ELEMENTE VAN REVOLUSIE - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The prerequisites for revolution can be divided into categories, according to the author of the article below. The most important categories are provocation, united public opinion, hope, a strong leader element and low morale. Examples are quoted of countries in which revolutions came to pass and the purpose of the article is to draw the attention of the reader to a certain pattern of occurrences and circumstances applicable to any country in which a revolutionary situation exists or has existed in the past.